ON THE STATE OF WATER SUPPLY KHARKIV - , Д. Ф., О. В., ХАЙНРИХ, А. И., Е. В. (Municipal economy of cities (Technical science), 2013)
The modern state of water supply Kharkov. Presented reasons for the high level of wear conduits and methods of recovery.